Question
upstudy study bank question image url

What is the reduced radical form of each expression? Assume all variables are positive. SEE EXAMPLE 2 23. \( \sqrt[3]{250 y^{2} z^{4}} \) \( \begin{array}{ll}\text { 25. } \frac{\sqrt{48 x^{3}}}{3 x y^{2}} & \text { 24. } \sqrt[4]{256 v^{7} w^{12}} \\ \text { 27. } \sqrt[3]{216 m} & \text { 26. } \sqrt{\frac{56 x^{5} y^{5}}{7 x y}} \\ \end{array} \)

Ask by Powell Coleman. in the United States
Feb 19,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the reduced radical forms of the given expressions: 1. \( \sqrt[3]{250 y^{2} z^{4}} = 5 z \sqrt[3]{2 y^{2} z} \) 2. \( \sqrt[4]{256 v^{7} w^{12}} = 4 v w^3 \sqrt[4]{v^3} \) 3. \( \frac{\sqrt{48 x^{3}}}{3 x y^{2}} = \frac{4 \sqrt{3x}}{3 y^{2}} \) 4. \( \sqrt{\frac{56 x^{5} y^{5}}{7 x y}} = 2 x^{2} y^{2} \sqrt{2} \) 5. \( \sqrt[3]{216 m} = 6 \sqrt[3]{m} \)

Solution

To find the reduced radical form of each expression, we will simplify them step by step. Let's start with each expression one by one. ### 23. \( \sqrt[3]{250 y^{2} z^{4}} \) 1. **Factor the radicand**: - \( 250 = 2 \times 125 = 2 \times 5^3 \) - So, \( 250 y^2 z^4 = 2 \times 5^3 \times y^2 \times z^4 \) 2. **Apply the cube root**: - \( \sqrt[3]{250 y^{2} z^{4}} = \sqrt[3]{2} \times \sqrt[3]{5^3} \times \sqrt[3]{y^2} \times \sqrt[3]{z^4} \) - \( \sqrt[3]{5^3} = 5 \) - \( \sqrt[3]{y^2} = y^{2/3} \) - \( \sqrt[3]{z^4} = z^{4/3} = z^{1} \times z^{1/3} \) 3. **Combine the results**: - \( \sqrt[3]{250 y^{2} z^{4}} = 5 z \sqrt[3]{2 y^{2} z} \) ### 24. \( \sqrt[4]{256 v^{7} w^{12}} \) 1. **Factor the radicand**: - \( 256 = 4^4 = 2^8 \) - So, \( 256 v^7 w^{12} = 2^8 \times v^7 \times w^{12} \) 2. **Apply the fourth root**: - \( \sqrt[4]{256 v^{7} w^{12}} = \sqrt[4]{2^8} \times \sqrt[4]{v^7} \times \sqrt[4]{w^{12}} \) - \( \sqrt[4]{2^8} = 2^2 = 4 \) - \( \sqrt[4]{v^7} = v^{7/4} = v^{1} \times v^{3/4} \) - \( \sqrt[4]{w^{12}} = w^{3} \) 3. **Combine the results**: - \( \sqrt[4]{256 v^{7} w^{12}} = 4 v w^3 \sqrt[4]{v^3} \) ### 25. \( \frac{\sqrt{48 x^{3}}}{3 x y^{2}} \) 1. **Simplify the numerator**: - \( 48 = 16 \times 3 = 4^2 \times 3 \) - So, \( \sqrt{48 x^{3}} = \sqrt{16 \times 3 \times x^3} = 4 \sqrt{3} \times x^{3/2} = 4 \sqrt{3} \times x \sqrt{x} \) 2. **Combine with the denominator**: - \( \frac{4 x \sqrt{3} \sqrt{x}}{3 x y^{2}} \) - Cancel \( x \) from numerator and denominator: - \( \frac{4 \sqrt{3} \sqrt{x}}{3 y^{2}} \) 3. **Final result**: - \( \frac{4 \sqrt{3x}}{3 y^{2}} \) ### 26. \( \sqrt{\frac{56 x^{5} y^{5}}{7 x y}} \) 1. **Simplify the fraction**: - \( \frac{56}{7} = 8 \) - \( \frac{x^5}{x} = x^{4} \) - \( \frac{y^5}{y} = y^{4} \) - So, \( \sqrt{\frac{56 x^{5} y^{5}}{7 x y}} = \sqrt{8 x^{4} y^{4}} \) 2. **Apply the square root**: - \( \sqrt{8} = 2 \sqrt{2} \) - \( \sqrt{x^{4}} = x^{2} \) - \( \sqrt{y^{4}} = y^{2} \) 3. **Combine the results**: - \( \sqrt{\frac{56 x^{5} y^{5}}{7 x y}} = 2 x^{2} y^{2} \sqrt{2} \) ### 27. \( \sqrt[3]{216 m} \) 1. **Factor the radicand**: - \( 216 = 6^3 \) - So, \( \sqrt[3]{216 m} = \sqrt[3]{6^3 \times m} = 6 \sqrt[3]{m} \) ### Summary of Results - \( \sqrt[3]{250 y^{2} z^{4}} = 5 z \sqrt[3]{2 y^{2} z} \) - \( \sqrt[4]{256 v^{7} w^{12}} = 4 v w^3 \sqrt[4]{v^3} \) - \( \frac{\sqrt{48 x^{3}}}{3 x y^{2}} = \frac{4 \sqrt{3x}}{3 y^{2}} \) - \( \sqrt{\frac{56 x^{5} y^{5}}{7 x y}} = 2 x^{2} y^{2} \sqrt{2} \) - \( \sqrt[3]{216 m} = 6 \sqrt[3]{m} \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To tackle these expressions, let's first simplify each one. For \( \sqrt[3]{250 y^{2} z^{4}} \), we can break it down: \( 250 = 2 \times 125 = 2 \times 5^3 \) and the radicals yield \( 5 \) from the \( 5^3 \), leaving \( 2 \) under the cube root, along with \( y^{2} \) and \( z^{4} = z^{3}z \), which provides \( z \) outside the root. Thus, the reduced radical form is \( 5z\sqrt[3]{2y^{2}z} \). For the expression \( \frac{\sqrt{48 x^{3}}}{3 x y^{2}} \), simplify the numerator first: \( \sqrt{48} = 4\sqrt{3} \) and \( \sqrt{x^{3}} = x\sqrt{x} \). So, we rewrite it as \( \frac{4x\sqrt{3x}}{3xy^{2}} \). Canceling out \( x \) in the numerator and denominator results in \( \frac{4\sqrt{3x}}{3y^{2}} \). Wasn't that fun? Now let's dive deeper into how these concepts are applied in everyday life! In architecture, understanding how to deal with radicals helps in calculating areas and volumes, especially when designing complex structures. Your math skills come in handy when optimizing spaces or figuring out material needs based on irregular shapes! Furthermore, awareness of common mistakes can elevate your mathematical prowess. When simplifying radicals, many forget to check for the highest perfect square or cube factor, leading to incomplete answers. Always ensure you're breaking down numbers correctly and double-check the indices for accuracy. Happy simplifying!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy